Dashboard Design for New Employee Candidate Program at XYZ Bank Using Tableau - Winona, Aisyah Vasthi; Siswanto, Teddy; Sugiarto, Dedy (Intelmatics, 2024)
Bank XYZ is a government-owned company engaged in the banking sector, requires data and information support to support decisions to be taken by Company leadership because the current system requires a fairly long process in presenting the supporting data. So this research aims to design a dashboard to make it easier for management to obtain important information for decision making. The research methodology uses a flow starting from problem identification, needs analysis, raw data acquisition, OLAP design, ETL process and visualization. This research uses Pentaho tools to carry out the ETL process and Tableau tools to create dashboards. Based on the OLAP design of this research, a fact table for the distribution of ODP and a dimension table consisting of location, trip, city, start date, end date, class, gender, university and major were formed. As a result of this research, the design that has been made means that dashboard users/managers can anticipate or detect early delays in the process of making a rundown for the next stage of the journey, users/managers of the dashboard can anticipate or detect early delays in the process of making a rundown for the next stage of the journey, can find out about universities and the most study programs for more precise decision making, and has a data filtering feature which is useful for searching for certain data more quickly so that the decision making process can be supported by the information produced.